Exploring Professional Ethics in a Competence-Based Curriculum Implementation at a Teacher’s College in Rwanda - Joseph Dzavo; Onias Musaniwa; James Maizere; Christopher Mutseekwa; Emmanuel Nduwayo (Scientia Publica Media, 2025)
Professional ethics are crucial for implementing quality education within any society, as they play a vital role in deploying educational programmes in learning institutions. With this in mind, the researchers identified challenges related to professional ethics faced by staff at a Teacher Training College in Rwanda while implementing a Competence-Based Curriculum (CBC). These observations prompted the researchers to investigate the impact of professional ethics within the implementation framework, alongside various other potential factors. A qualitative approach and a single case study design were employed. Participants were purposively selected from the chosen Teacher Training College(TTC) in the Eastern Province for semi-structured interviews with six tutors. Ten student teachers were also purposively sampled for a focus group interview. Observations of tutors’ daily routines were conducted, and document analysis was utilised. The data generated were analysed thematically. The study was guided by Rogan and Grayson’s (2003) theory of Curriculum Implementation (CI) and Rest’s (1983) four-component model (FCM) of morality. The findings revealed that tutors’ professional conduct influenced their commitment to duty, preparation, methodology, and punctuality. Furthermore, the study established that tutors were not adequately equipped with professional ethics to interpret and implement the CBC in line with 21st-century trends. Additional findings indicated that tutors rarely related their teaching actions to ethical principles. Last but not least, student teachers had expectations of modelling best practices from their tutors. Fulfilled expectations would see effective CBC implementation. The study concluded that a lack of professional ethics in tutors affects effective CBC implementation in the TTC. Some recommendations include ongoing professional development to enhance the tutors’ cognitive and dialogical competencies necessary for reflecting on their actions, and equipping them with ethical reasoning and professional responsibility. Finally, the Government of Rwanda is urged to revisit the Tutors’ training curriculum to enhance professional undertakings.